EU Regional Policy and the Neighbour's Curse: Analyzing the Income Convergence Effects of ESIF Funding in the Presence of Spatial Spillovers. (30th November 2018) - Breidenbach, Philipp; Mitze, Timo; Schmidt, Christoph M.
Abstract: The European structural and investment funds (ESIF) constitute the prime instrument of EU regional policy. We study the ESIF's effectiveness in terms of fostering intra‐EU income convergence through investment support to lagging regions. Our empirical results for the period 1997–2007 indicate that the ESIF's contribution to income growth is insignificant or even negative for several peripheral EU regions. We argue that the negative link between funding and regional growth is mainly attributable to spatial spillovers. While the latter may reflect the intensified competition for scarce production factors among highly funded regions in geographical proximity, we also discuss the role played by structural backwardness in a macro‐regional context to explain this sobering result. As such, we show that negative funding effects significantly correlate with lower levels of regional institutional quality. Taken together, our findings indicate that unintended distortionary effects restrain EU regional policy from working effectively to foster income convergence.